2018
DOI: 10.1158/0008-5472.can-17-2761
|View full text |Cite
|
Sign up to set email alerts
|

HER2 Overexpression Triggers an IL1α Proinflammatory Circuit to Drive Tumorigenesis and Promote Chemotherapy Resistance

Abstract: Systemic inflammation in breast cancer correlates with poor prognosis, but the molecular underpinnings of this connection are not well understood. In this study, we explored the relationship between HER2 overexpression, inflammation, and expansion of the mammary stem/progenitor and cancer stem-like cell (CSC) population in breast cancer. HER2-positive epithelial cells initiated and sustained an inflammatory milieu needed to promote tumorigenesis. HER2 induced a feedforward activation loop of IL1α and IL6 that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 45 publications
(53 reference statements)
4
71
0
Order By: Relevance
“…838 upregulated and 536 downregulated genes by HER2 overexpression were obtained using cutoff of actual fold change of 1.5 (FC >=1.5 or <=-1.5) and adjusted p value of less than 0.05 (Supplemental Table 2). Gene Set Enrichment Analysis (GSEA) (Subramanian et al, 2005) analysis with Hallmark pathways revealed that HER2-regulated genes are significantly enriched in 18 pathways such as TNFα signaling, EMT transition, inflammatory response and mTOR ( Figure 3C and Supplemental Table 5), consistent with previous reports with similar set up (Dong et al, 2017;Liu et al, 2018b;Pradeep et al, 2012). PHF8 knockdown attenuated most of the pathways induced by HER2 overexpression ( Figure 3C and Supplemental Table 6).…”
Section: Phf8 Has Dominant Coactivator Function Downstream Of Her2 Sisupporting
confidence: 89%
“…838 upregulated and 536 downregulated genes by HER2 overexpression were obtained using cutoff of actual fold change of 1.5 (FC >=1.5 or <=-1.5) and adjusted p value of less than 0.05 (Supplemental Table 2). Gene Set Enrichment Analysis (GSEA) (Subramanian et al, 2005) analysis with Hallmark pathways revealed that HER2-regulated genes are significantly enriched in 18 pathways such as TNFα signaling, EMT transition, inflammatory response and mTOR ( Figure 3C and Supplemental Table 5), consistent with previous reports with similar set up (Dong et al, 2017;Liu et al, 2018b;Pradeep et al, 2012). PHF8 knockdown attenuated most of the pathways induced by HER2 overexpression ( Figure 3C and Supplemental Table 6).…”
Section: Phf8 Has Dominant Coactivator Function Downstream Of Her2 Sisupporting
confidence: 89%
“…This analysis, rank‐ordered by P value, identifies a strong proinflammatory cytokine signature (Figure B). Two IL‐1 family members (IL‐1α and IL‐1β), IL‐6, as well as STAT3, a transcription factor downstream of all three cytokines, are found in the top seven predicted upstream regulators with activation Z ‐scores of 4.286, 3.881, 3.667, and 2.367, respectively (Figure B). These data strongly suggest that BHLHE40‐AS1 plays an important role in inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Further, while less studied in cancer than IL‐1β, IL‐1α has been found to support inflammation and cancer stem cell expansion downstream of HER2 expression. IL‐1α induces IL‐6 and STAT3 signaling creating a feed‐forward proinflammation signaling loop supporting tumor progression …”
Section: Discussionmentioning
confidence: 99%
“… 116 The precancerous effect of HER2 was also found to be linked to inflammation and the expansion of cancer stem-like cells (CSCs) in breast cancer. 117 A newly identified enhancer located at the 3′ gene body of HER2 was reported to be the target locus of known HER2 regulator, TFAP2C. 118 Other epigenetic mechanisms, such as DNA methylation and histone modifications, also affect this process.…”
Section: Major Signaling Pathways In Breast Cancer Development and Prmentioning
confidence: 99%